2021
DOI: 10.1186/s12885-021-08034-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the potential novel biomarkers as susceptibility gene for Wilms tumor

Abstract: Background Wilms tumor (WT) is the most common malignant renal tumor in children. The aim of this study was to identify potential susceptibility gene of WT for better prognosis. Methods Weighted gene coexpression network analysis is used for the detection of clinically important biomarkers associated with WT. Results In the study, 59 tissue samples from National Cancer Institute were pretreated for con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Despite advances in treatment strategies and the favorable prognosis of most patients with WT, the mortality rate is still 10% ( 9 ). Poor outcomes have been reported for advanced, bilateral and recurrent WT ( 10 ). Therefore, it is critical to identify novel prognostic factors for WT to guide the development of individualized treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in treatment strategies and the favorable prognosis of most patients with WT, the mortality rate is still 10% ( 9 ). Poor outcomes have been reported for advanced, bilateral and recurrent WT ( 10 ). Therefore, it is critical to identify novel prognostic factors for WT to guide the development of individualized treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…WGCNA, a scale-free network distribution approach, is powerful data-driven tool to study gene expression pattern in samples from different cohorts [ 77 ]. Using WGCNA, we were able to validate the DEG pathway signatures in BWS-WT.…”
Section: Discussionmentioning
confidence: 99%
“…Modules enriched for altered-11p15 nonBWS-WT trait mainly showed enrichment of cell cycle and metabolic processes. Many other studies on WT using the WGCNA approach have showed enrichment of cell cycle related processes, indicating it as a major molecular signature for WT [ 77 79 ]. Along with metabolic pathway enrichment, Wang et al have also shown enrichment of PI3K-Akt, FoxO, p53, and TNF signaling pathways, along with many other cancer related pathways in WT, using the WGCNA approach [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nephroblastoma is the most common childhood abdominal malignancy and approximately 15% of patients will experience recurrence with a 40 to 80% overall survival rate [21]. Although the diagnosis and therapeutic effects have significantly improved, long-term survival rate remains low in patients with nephroblastoma with high mortality rate [22].…”
Section: Discussionmentioning
confidence: 99%